Dead-Time Distortion in Generalized Selective Harmonic Control - Khaligh, A.; Wells, J.R.; Chapman, P.L.; Krein, P.T. (IEEE transactions on power electronics, 2008)
The selective harmonic control (SHC) method of pulsewidth modulation is meant to place switching edges to eliminate or set precisely given harmonics. This manuscript discusses the practical impact of edge placement sensitivity due to dead time that occurs in generalized SHC. It further provides experimental validation to theoretical work presented in a previous publication.